Frequency and genotype distribution of high-risk human papilloma virus types in Karabuk province, Turkey: A hospital based cross-sectional study (Annals of Medical Research, 2021)
Aim: In this cross-sectional study, we aimed to determine the prevalence and genotype distribution of high-risk human papillomavirus (HPV; HR-HPV) infection in patients admitted to the gynecology and obstetrics outpatient clinics of Karabuk University Training and Research Hospital.Material and Methods: A total of 402 women aged 18–65 years who were admitted to the gynecology and obstetrics Clinic, Karabuk University Training and Research Hospital, between October 2016 and June 2019 were included. The presence of HR-HPV and genotyping of HPV were investigated using real-time polymerase chain reaction in cervical swab samples.Results: HR-HPV infection was found in 23.9% of women. HR-HPV positivity was detected most commonly in the age group of 20–29 years. Regarding genotype distribution among HPV-positive women, the genotypes that included multiple HR-HPV infections (mixed HR-HPV) were the most common genotype (38.5%), followed by HPV-16 (13.1%) and HPV-52 (9.8%).Conclusion: Prevalence of HR-HPV infection was found to be high in our region, with the most commonly observed genotypes being those containing mixed HR-HPV. We believe that these results would be helpful during the selection of primary and secondary preventive measures for cervical cancer while planning vaccination and screening programs.
Keywords: HPV; HR- HPV Types; cervical cancer